Investigating the Interplay of Information, Motivation, and Behavioral Skills in Shaping the Work Performance of the Stunting Reduction Acceleration Team in Karanganyar - Mahzunah, Amalia Khurotul; Hastuti, Heni; Putri, Anak Agung Alit Kirti Estuti Narendra; Sulaeman, Endang Sutisna; Rahman, Abdul (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Stunting is a significant issue both globally and nationally. In Karanganyar, an area with a high stunting risk, the performance of the stunting reduction acceleration team is crucial. The information, motivation, and behavioral skill (IMB) model can help explain improvements in individual performance. This study aims to examine the relationships between information, motivation, and behavioral skills and the work performance of the stunting reduction acceleration team in Karanganyar.Methods: This quantitative research uses a cross-sectional design and includes 213 team members selected through simple random sampling in 2023. Data were analyzed using univariate, bivariate, and multivariate methods.Results: The findings indicate that behavioral skills (p = 0.027) show significant positive correlations with work performance. However, there is no significant correlation between information (p = 0.646) and work performance, as does motivation (p = 0.757). The overall interaction model is not significant (p = 0.677).Conclusion: In summary, behavioral skills alone show a positive relationship with performance, whereas information and motivation do not. Collectively, information, motivation, and behavioral skills do not significantly impact the performance of the stunting reduction acceleration team. To enhance team performance, it is essential to prioritize training that develops behavioral skills, alongside providing structured information and implementing motivational strategies, such as rewards and recognition, to sustain team engagement.